(untitled) (Research, Society and Development, 2022)
The purpose of the present study was to review the evidence on the effect of strength training on elderly quality-of-life. The search was carried out in Scielo database and include research published between 2010 and december 2021. A total of 259 research was found. It was performed the inclusion and exclusion criteria and 4 articles were analyzed and included in this review. All articles included indicate positive effects of strength training on elderly quality-of-life, indicating effectiveness in several dimensions considered for the quality-of-life assessment. It is concluded that strength training is important to improve quality in various aspects of your life, which is why it is important. Thus, the data found allow us to conclude that physical activity is one of the main contributing factors for a better quality of life.